Room-temperature silane-crosslinked, low-smoke, halogen-free and flame-retardant cable material and preparation method thereof
By using room temperature silane crosslinking technology and optimized formulation processes, the problems of high energy consumption and poor flame retardant dispersibility in silane crosslinked low-smoke halogen-free polyolefin cable materials have been solved, achieving high efficiency in flame retardant performance and improved mechanical properties.
Patent Information
- Application Number
- CN202511225392.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-29
- Publication Date
- 2025-11-18
AI Technical Summary
The preparation of existing silane crosslinked low-smoke halogen-free polyolefin cable materials suffers from high energy consumption, complex equipment, and poor flame retardant dispersion, leading to a decline in mechanical properties and making it difficult to achieve both flame retardant and mechanical properties.
By employing room temperature silane crosslinking technology and combining low-smoke halogen-free masterbatch with grafted masterbatch, the formulation system and process are optimized to achieve uniform dispersion of flame retardants. A two-component catalytic system is used for self-crosslinking, simplifying equipment configuration.
It reduces energy consumption, improves the dispersion uniformity and compatibility of flame retardants, enhances the flame retardant and mechanical properties of cable materials, and possesses excellent comprehensive performance.
Smart Images

Figure BDA0005572510430000121
Abstract
Description
Technical Field
[0001] This application relates to the technical field of cable materials, and in particular to a room temperature silane crosslinked, low-smoke, halogen-free flame-retardant cable material and its preparation method. Background Technology
[0002] With the increasing global awareness of environmental protection and the ever-increasing requirements for the safety of materials, the performance indicators of cable materials, as a core component of cable products, have become a key factor affecting the application scope and safety of cables. Traditional cable materials easily release large amounts of toxic fumes and corrosive gases during combustion, which not only poses a serious threat to human health but also has a destructive impact on surrounding equipment and the environment, making it difficult to meet the stringent requirements for the environmental protection and safety of cable materials in current technologies.
[0003] Silane cross-linked low-smoke halogen-free polyolefin cable materials have become an important direction for material upgrading and technological development in the current cable industry due to their excellent environmental performance, such as low smoke emission and no release of toxic and harmful gases during combustion, as well as their advantages such as high mechanical strength, good thermal stability and aging resistance.
[0004] However, in the preparation and application of silane crosslinked low-smoke halogen-free polyolefin cable materials, there are still some technical problems that need to be solved in the existing technology: On the one hand, the high-temperature crosslinking process used in the preparation of this type of cable material has high energy consumption, requires complex equipment structure and high investment cost; on the other hand, in order to improve the flame retardant performance of the cable material, flame retardants and other additives need to be added to the resin material, but the dispersion uniformity of the flame retardant in the resin material is poor and the compatibility between the flame retardant and the resin material is insufficient, which can easily lead to a significant decrease in the mechanical properties of the cable material. It is impossible to take into account both the flame retardant performance and the mechanical properties of the material, which further limits the performance improvement and application expansion of the cable material.
[0005] Therefore, how to improve the mechanical strength of cable materials while ensuring good flame retardant effect has become an urgent problem to be solved in the field of cable material research and development. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this application provides a room-temperature silane crosslinked, low-smoke, halogen-free flame-retardant cable material and its preparation method.
[0007] In a first aspect, this application provides a room-temperature silane crosslinked, low-smoke, halogen-free flame-retardant cable material, employing the following technical solution: A room-temperature silane crosslinked, low-smoke halogen-free flame-retardant cable material includes cable material A and cable material B; said cable material A includes low-smoke halogen-free masterbatch and grafted masterbatch. The low-smoke halogen-free masterbatch comprises the following raw material components in parts by weight: 50-70 parts of ethylene-vinyl acetate copolymer, 15-25 parts of polyolefin elastomer, 5-15 parts of linear low-density polyethylene, 160-200 parts of active inorganic flame retardant, 5-15 parts of compatibilizer, 1.5-2.5 parts of silicone masterbatch, 0.5-1.5 parts of polyethylene wax, 1.5-2.5 parts of carbon black, and 2-4 parts of antioxidant.
[0008] The grafted masterbatch comprises the following raw material components in parts by weight: 10-30 parts of ethylene-vinyl acetate copolymer, 10-20 parts of metallocene polyethylene, 50-70 parts of linear low-density polyethylene, and 1-3 parts of silane coupling agent.
[0009] By adopting the above technical solution, this application incorporates low-smoke halogen-free masterbatch and grafted masterbatch. The low-smoke masterbatch provides environmentally friendly flame retardancy, while the grafted masterbatch enhances dispersion, interfacial bonding, and functionality. Through the functional complementarity and interfacial synergy between the two, performance improvement is achieved, thereby obtaining cable material with flame-retardant properties.
[0010] This application adopts a formulation system combination. The types and combination ratios of resin materials and flame retardant systems are determined through testing, and the proportions of added additives are screened to ensure that all components are mixed evenly.
[0011] This application achieves self-crosslinking at room temperature through a two-component catalytic system, which significantly reduces energy consumption and simplifies equipment configuration.
[0012] This application optimizes the formulation and process, maintains good mechanical properties, increases tensile strength, effectively improves the dispersion uniformity of flame retardants in resin materials, improves the compatibility of flame retardants with resin materials and other raw materials, and enhances the mechanical properties of the materials.
[0013] Preferably, the cable material B comprises the following raw material components in parts by weight: 50-70 parts of ethylene-vinyl acetate copolymer, 25-35 parts of linear low-density polyethylene, 140-160 parts of active inorganic flame retardant, 5-15 parts of compatibilizer, 1-3 parts of silicone masterbatch, 3-5 parts of stearic acid, 1-2 parts of carbon black, 2-4 parts of antioxidant, and 3-5 parts of organotin.
[0014] Preferably, the active inorganic flame retardant is at least one of aluminum hydroxide and magnesium hydroxide.
[0015] Preferably, the antioxidant is at least one of antioxidant 1024, antioxidant 300, and antioxidant DLTDP.
[0016] Preferably, the low-smoke halogen-free masterbatch further includes 20-30 parts by weight of flame-retardant composite material, wherein the flame-retardant composite material comprises the following raw material components in parts by weight: 45-55 parts of ammonium polyphosphate, 0.5-1.5 parts of alkylphenol polyoxyethylene ether, 5-15 parts of tetraethyl orthosilicate, 10-20 parts of aluminum hydroxide, 0.5-1.5 parts of carboxymethyl chitosan, 0.01-0.1 parts of magnesium hydroxide, and 1-2 parts of silane coupling agent.
[0017] By adopting the above technical solution, the improvement of raw materials and the addition of flame-retardant composite materials in this application can effectively improve the stability of cable materials at high temperatures, reduce the heat release rate and total heat release of cable materials, and further improve the flame-retardant performance of cable materials.
[0018] Preferably, the preparation method of the flame-retardant composite material includes the following steps: Ammonium polyphosphate and alkylphenol polyoxyethylene ether were mixed, then tetraethyl orthosilicate was added and mixed again, followed by the addition of aluminum hydroxide and the mixture was filtered to obtain the first mixture. Carboxymethyl chitosan was dissolved in water to obtain a carboxymethyl chitosan solution; Magnesium hydroxide is dissolved in ethanol to obtain a magnesium hydroxide solution; The carboxymethyl chitosan solution and magnesium hydroxide solution were mixed and then centrifuged to obtain a second mixture. The first mixture, the second mixture, and the silane coupling agent are mixed to obtain a flame-retardant composite material.
[0019] By adopting the above technical solution, the product prepared in this application using ammonium polyphosphate, alkylphenol polyoxyethylene ether, and tetraethyl orthosilicate as raw materials is then mixed with aluminum hydroxide. The product and aluminum hydroxide can delay combustion through a condensed phase-gas phase synergistic flame retardant mechanism, thereby preparing a first mixture with thermal stability and flame retardant properties.
[0020] In this application, carboxymethyl chitosan is used to microencapsulate and modify magnesium hydroxide flame retardant. Carboxymethyl chitosan encapsulates magnesium hydroxide through hydrogen bonds, resulting in a second mixture with good dispersibility and flame retardant properties. A flame-retardant composite material with flame-retardant properties was prepared by using a first mixture and a second mixture in the presence of a silane coupling agent.
[0021] Preferably, the cable material B further includes 10-15 parts by weight of a flame retardant additive, which comprises the following raw material components in parts by weight: 1-3 parts of chitosan oligosaccharide, 25-35 parts of tetrahydrofuran, 30-40 parts of triethylamine, 3-7 parts of phenylphosphodichloro, 1-5 parts of furfurylamine, and 40-60 parts of petroleum ether.
[0022] Preferably, the preparation method of the flame retardant additive includes the following steps: Chitosan oligosaccharide, tetrahydrofuran, and triethylamine were mixed, followed by the addition of phenylphosphodichloro, then furfurylamine, and finally petroleum ether. The mixture was then filtered to obtain the flame retardant additive.
[0023] By adopting the above technical solution, this application synthesizes a flame retardant additive through the substitution reaction of furfurylamine with chitosan oligosaccharide and phenylphosphodichloro. By improving the raw materials and adding the flame retardant additive, this application effectively reduces the peak heat release rate, total heat release and average effective heat of combustion of the cable material, thereby further improving the flame retardant performance of the cable material.
[0024] Preferably, the mass ratio of the low-smoke halogen-free masterbatch to the grafted masterbatch is (10-30):(90-70).
[0025] Secondly, this application provides a method for preparing a room-temperature silane crosslinked, low-smoke, halogen-free flame-retardant cable material, employing the following technical solution: A method for preparing a room-temperature silane crosslinked, low-smoke, halogen-free flame-retardant cable material, comprising the following steps: Preparation of cable material A: After uniformly mixing ethylene-vinyl acetate copolymer, polyolefin elastomer, linear low-density polyethylene, active inorganic flame retardant, polyethylene wax, carbon black, antioxidant, and flame retardant composite material, compatibilizer and silicone masterbatch are added and mixed to obtain low-smoke halogen-free masterbatch. Ethylene-vinyl acetate copolymer, metallocene polyethylene, linear low-density polyethylene, and silane coupling agent are mixed and homogenized to obtain graft masterbatch. Low-smoke halogen-free masterbatch and grafted masterbatch are fed into a screw extruder for extrusion and granulation to obtain cable material A. Preparation of cable material B: After uniformly mixing ethylene-vinyl acetate copolymer, linear low-density polyethylene, active inorganic flame retardant, stearic acid, carbon black, antioxidant, organotin, and flame retardant additive, compatibilizer and silicone masterbatch are added and mixed. The mixture is then fed into a screw extruder for extrusion granulation to obtain cable material B. Preparation of cable materials: Cable material A and cable material B are fed into a screw extruder for extrusion and granulation to obtain cable material.
[0026] By adopting the above technical solution, this application improves the raw materials by mixing low-smoke halogen-free masterbatch and grafted masterbatch to prepare cable material A; by mixing cable material A and cable material B, the prepared cable material has stable and efficient flame retardant and smoke-suppressing properties, high mechanical strength, and excellent comprehensive performance, and has important application value in the field of cable material technology.
[0027] This application improves the dispersion uniformity of flame retardants through layered coating technology, enabling the prepared cable material to have low smoke and halogen-free flame retardant properties, low smoke density, and no halogen acid gas release.
[0028] This application employs a mixing process, including internal mixer mixing process design and screw extruder process design, to ensure the mixing and dispersion effect of each component; this application also employs a powder premixing and processing process to ensure the uniformity of each component.
[0029] In summary, this application includes at least one of the following beneficial technical effects: This application discloses a room-temperature silane crosslinked, low-smoke, halogen-free flame-retardant cable material and its preparation method. The prepared cable material has good flame-retardant effect, high mechanical strength, and excellent comprehensive performance. Detailed Implementation
[0030] The technical solutions of this application are further illustrated by specific embodiments below. These specific embodiments do not represent a limitation on the scope of protection of this application. Any non-essential modifications and adjustments made by others based on the concept of this application still fall within the scope of protection of this application.
[0031] All raw materials involved in this application are commercially available products, among which, Ammonium polyphosphate, CAS No. 68333-79-9, was purchased from Nantong Zhonghe Chemical New Materials Co., Ltd. Alkylphenol polyoxyethylene ether, OP-10, purchased from Sinopharm Chemical Reagent Co., Ltd. Tetraethyl orthosilicate, purchased from Sinopharm Chemical Reagent Co., Ltd. Chitosan oligosaccharide, 99.0%, purchased from Shandong Yatu Biotechnology Co., Ltd.; Petroleum ether, purchased from Tianjin Fuyu Fine Chemical Co., Ltd. Ethylene-vinyl acetate copolymer, grade: V6110MC, purchased from BASF Yangzi; Polyolefin elastomer, brand name: DF110, purchased from Mitsui Chemicals; Linear low-density polyethylene, grade: DFDA-7042; Aluminum hydroxide, grade: AH-01DG, purchased from Luoyang Zhongchao New Materials Co., Ltd. Magnesium hydroxide, brand name: MAGNIFIN H-5, purchased from Albemarle; Compatibilizer, brand name: AC2116, purchased from DuPont, USA; Silicone masterbatch, brand name: HMB-6301, purchased from DuPont, USA; Polyethylene wax, grade: SX-10B, purchased from Yanshan Petrochemical; Carbon black, grade: N550; Metallocene polyethylene, grade: 3518CB, purchased from ExxonMobil; Stearic acid, grade: 1810; Organotin, grade: MT101.
[0032] The present application will be further described in detail below with reference to embodiments and comparative examples.
[0033] Preparation Example 1: Preparation of flame-retardant composite materials: The flame-retardant composite material comprises the following raw material components: 50 kg of ammonium polyphosphate, 1 kg of alkylphenol polyoxyethylene ether, 10 kg of tetraethyl orthosilicate, 15 kg of aluminum hydroxide, 1 kg of carboxymethyl chitosan, 0.05 kg of magnesium hydroxide, and 1.5 kg of silane coupling agent KH550.
[0034] The preparation method of flame-retardant composite materials includes the following steps: Ammonium polyphosphate, alkylphenol polyoxyethylene ether, 150 mL ethanol, and 100 mL deionized water were mixed at 45 °C for 20 minutes. Ammonia was added to adjust the pH to 10. Tetraethyl orthosilicate was added and mixed at 45 °C for 1 hour. Aluminum hydroxide was then added and mixed for 30 minutes. The mixture was filtered to obtain the first mixture. Carboxymethyl chitosan was dissolved in 100 mL of water and stirred evenly at 75 °C to obtain a carboxymethyl chitosan solution; magnesium hydroxide was dissolved in 100 mL of anhydrous ethanol and ultrasonically dispersed for 20 minutes to obtain a magnesium hydroxide solution. The carboxymethyl chitosan solution and magnesium hydroxide solution were mixed and reacted at 130°C for 2 hours, then centrifuged to obtain a second mixture. The first mixture, the second mixture, and the silane coupling agent KH550 were mixed for 3 hours to obtain a flame-retardant composite material.
[0035] Preparation Example 2: Preparation of flame-retardant composite materials: The flame-retardant composite material comprises the following raw material components: 45 kg of ammonium polyphosphate, 0.5 kg of alkylphenol polyoxyethylene ether, 5 kg of tetraethyl orthosilicate, 10 kg of aluminum hydroxide, 0.5 kg of carboxymethyl chitosan, 0.01 kg of magnesium hydroxide, and 1 kg of silane coupling agent KH550.
[0036] The preparation method of flame-retardant composite materials includes the following steps: Ammonium polyphosphate, alkylphenol polyoxyethylene ether, 150 mL ethanol, and 100 mL deionized water were mixed at 45 °C for 20 minutes. Ammonia was added to adjust the pH to 10. Tetraethyl orthosilicate was added and mixed at 45 °C for 1 hour. Aluminum hydroxide was then added and mixed for 30 minutes. The mixture was filtered to obtain the first mixture. Carboxymethyl chitosan was dissolved in 100 mL of water and stirred evenly at 75 °C to obtain a carboxymethyl chitosan solution; magnesium hydroxide was dissolved in 100 mL of anhydrous ethanol and ultrasonically dispersed for 20 minutes to obtain a magnesium hydroxide solution. The carboxymethyl chitosan solution and magnesium hydroxide solution were mixed and reacted at 130°C for 2 hours, then centrifuged to obtain a second mixture. The first mixture, the second mixture, and the silane coupling agent KH550 were mixed for 3 hours to obtain a flame-retardant composite material.
[0037] Preparation Example 3: Preparation of flame-retardant composite materials: The flame-retardant composite material comprises the following raw material components: 55 kg of ammonium polyphosphate, 1.5 kg of alkylphenol polyoxyethylene ether, 15 kg of tetraethyl orthosilicate, 20 kg of aluminum hydroxide, 1.5 kg of carboxymethyl chitosan, 0.1 kg of magnesium hydroxide, and 2 kg of silane coupling agent KH550.
[0038] The preparation method of flame-retardant composite materials includes the following steps: Ammonium polyphosphate, alkylphenol polyoxyethylene ether, 150 mL ethanol, and 100 mL deionized water were mixed at 45 °C for 20 minutes. Ammonia was added to adjust the pH to 10. Tetraethyl orthosilicate was added and mixed at 45 °C for 1 hour. Aluminum hydroxide was then added and mixed for 30 minutes. The mixture was filtered to obtain the first mixture. Carboxymethyl chitosan was dissolved in 100 mL of water and stirred evenly at 75 °C to obtain a carboxymethyl chitosan solution; magnesium hydroxide was dissolved in 100 mL of anhydrous ethanol and ultrasonically dispersed for 20 minutes to obtain a magnesium hydroxide solution. The carboxymethyl chitosan solution and magnesium hydroxide solution were mixed and reacted at 130°C for 2 hours, then centrifuged to obtain a second mixture. The first mixture, the second mixture, and the silane coupling agent KH550 were mixed for 3 hours to obtain a flame-retardant composite material.
[0039] Preparation Example 4: Preparation of flame retardant additives: The flame retardant additives include the following raw material components: 2 kg of chitosan oligosaccharide, 30 kg of tetrahydrofuran, 35 kg of triethylamine, 5 kg of phenylphosphodichloro, 3 kg of furfurylamine, and 50 kg of petroleum ether.
[0040] The preparation method of flame retardant additives includes the following steps: Under nitrogen atmosphere, chitosan oligosaccharide, tetrahydrofuran, and triethylamine were mixed and reacted at 50°C for 30 minutes. Phenylphosphoryl dichloride was added and reacted at 50°C for 5 hours. Then, furfurylamine was added and reacted at 50°C for 3 hours. Finally, petroleum ether was added and reacted at 50°C for 30 minutes. The mixture was then filtered to obtain the flame retardant additive.
[0041] Preparation Example 5: Preparation of flame retardant additives: The flame retardant additives include the following raw material components: 1 kg of chitosan oligosaccharide, 25 kg of tetrahydrofuran, 30 kg of triethylamine, 3 kg of phenylphosphodichloro, 1 kg of furfurylamine, and 40 kg of petroleum ether.
[0042] The preparation method of flame retardant additives includes the following steps: Under nitrogen atmosphere, chitosan oligosaccharide, tetrahydrofuran, and triethylamine were mixed and reacted at 50°C for 30 minutes. Phenylphosphoryl dichloride was added and reacted at 50°C for 5 hours. Then, furfurylamine was added and reacted at 50°C for 3 hours. Finally, petroleum ether was added and reacted at 50°C for 30 minutes. The mixture was then filtered to obtain the flame retardant additive.
[0043] Preparation Example 6: Preparation of flame retardant additives: The flame retardant additives include the following raw material components: 3 kg of chitosan oligosaccharide, 35 kg of tetrahydrofuran, 40 kg of triethylamine, 7 kg of phenylphosphodichloro, 5 kg of furfurylamine, and 60 kg of petroleum ether.
[0044] The preparation method of flame retardant additives includes the following steps: Under nitrogen atmosphere, chitosan oligosaccharide, tetrahydrofuran, and triethylamine were mixed and reacted at 50°C for 30 minutes. Phenylphosphoryl dichloride was added and reacted at 50°C for 5 hours. Then, furfurylamine was added and reacted at 50°C for 3 hours. Finally, petroleum ether was added and reacted at 50°C for 30 minutes. The mixture was then filtered to obtain the flame retardant additive.
[0045] Example 1: A method for producing a room-temperature silane crosslinked, low-smoke, halogen-free flame-retardant cable material, comprising the following steps: 1. Preparation of cable material A: (1) Preparation of low-smoke halogen-free masterbatch: After mixing 60 kg of ethylene-vinyl acetate copolymer, 20 kg of polyolefin elastomer, 10 kg of linear low-density polyethylene, 180 kg of active inorganic flame retardant, 1 kg of polyethylene wax, 2 kg of carbon black, 2.5 kg of antioxidant, and 25 kg of flame retardant composite material evenly, add 10 kg of compatibilizer and 2 kg of silicone masterbatch and mix to obtain low-smoke halogen-free masterbatch. The active inorganic flame retardant is a mixture of 120 kg of aluminum hydroxide and 60 kg of magnesium hydroxide. The antioxidant is a mixture of 1.5 kg of antioxidant 1024 and 1 kg of antioxidant 300; The flame-retardant composite material was prepared as described in Preparation Example 1.
[0046] (2) Preparation of grafted masterbatch: 25 kg of ethylene-vinyl acetate copolymer, 15 kg of metallocene polyethylene, 60 kg of linear low-density polyethylene, and 2 kg of silane coupling agent were mixed and stirred to obtain graft masterbatch. Among them, the silane coupling agent is silane coupling agent A171; (3) Preparation of cable material A: Low-smoke halogen-free masterbatch and grafted masterbatch are fed into a screw extruder for extrusion and granulation to obtain cable material A. The twin-screw extruder has a length-to-diameter ratio of 44:1; the temperatures of each section of the twin-screw extruder are as follows: 80℃~100℃, 125℃~130℃, 130℃~135℃, 135℃~140℃, 140℃~145℃, 145℃~150℃, 150℃~155℃; the die head temperature is 145℃~150℃; and the screw speed is 550 rpm.
[0047] The mass ratio of low-smoke halogen-free masterbatch to grafted masterbatch is 20:80.
[0048] 2. Preparation of cable material B: 60 kg of ethylene-vinyl acetate copolymer, 30 kg of linear low-density polyethylene, 150 kg of active inorganic flame retardant, 4 kg of stearic acid, 2 kg of carbon black, 3 kg of antioxidant, 4 kg of organotin, and 13 kg of flame retardant additive were mixed evenly. Then, 10 kg of compatibilizer and 2 kg of silicone masterbatch were added and mixed. The mixture was then fed into a screw extruder for extrusion granulation to obtain cable material B. The twin-screw extruder has a length-to-diameter ratio of 44:1; the temperatures of each section of the twin-screw extruder are as follows: 80℃~100℃, 125℃~130℃, 130℃~135℃, 135℃~140℃, 140℃~145℃, 145℃~150℃, 150℃~155℃; the die head temperature is 145℃~150℃; and the screw speed is 550 rpm. Among them, the active inorganic flame retardant is aluminum hydroxide; The antioxidant is a mixture of antioxidant 1024 1.5kg, antioxidant 300 1kg, and antioxidant DLTDP 0.5kg; The flame retardant additive was prepared in Preparation Example 4.
[0049] 3. Preparation of cable material: Cable material A and cable material B are fed into a screw extruder for extrusion and granulation to obtain cable material; the length-to-diameter ratio of the twin-screw extruder is 44:1; the temperatures of each section of the twin-screw extruder are as follows: 80℃~100℃, 125℃~130℃, 130℃~135℃, 135℃~140℃, 140℃~145℃, 145℃~150℃, 150℃~155℃; the die head temperature is 145℃~150℃; and the screw speed is 550 rpm.
[0050] Example 2: A method for producing a room-temperature silane crosslinked, low-smoke, halogen-free flame-retardant cable material, comprising the following steps: 1. Preparation of cable material A: (1) Preparation of low-smoke halogen-free masterbatch: After mixing 50 kg of ethylene-vinyl acetate copolymer, 15 kg of polyolefin elastomer, 5 kg of linear low-density polyethylene, 160 kg of active inorganic flame retardant, 0.5 kg of polyethylene wax, 1.5 kg of carbon black, 2 kg of antioxidant, and 20 kg of flame retardant composite material evenly, 5 kg of compatibilizer and 1.5 kg of silicone masterbatch are added and mixed to obtain low-smoke halogen-free masterbatch. The active inorganic flame retardant is a mixture of 100 kg of aluminum hydroxide and 60 kg of magnesium hydroxide. The antioxidant is a mixture of 1 kg of antioxidant 1024 and 1 kg of antioxidant 300; The flame-retardant composite material was prepared in Preparation Example 2.
[0051] (2) Preparation of grafted masterbatch: 10 kg of ethylene-vinyl acetate copolymer, 10 kg of metallocene polyethylene, 50 kg of linear low-density polyethylene, and 1 kg of silane coupling agent were mixed and stirred to obtain graft masterbatch. Among them, the silane coupling agent is silane coupling agent A171; (3) Preparation of cable material A: Low-smoke halogen-free masterbatch and grafted masterbatch are fed into a screw extruder for extrusion and granulation to obtain cable material A. The twin-screw extruder has a length-to-diameter ratio of 44:1; the temperatures of each section of the twin-screw extruder are as follows: 80℃~100℃, 125℃~130℃, 130℃~135℃, 135℃~140℃, 140℃~145℃, 145℃~150℃, 150℃~155℃; the die head temperature is 145℃~150℃; and the screw speed is 550 rpm. The mass ratio of low-smoke halogen-free masterbatch to grafted masterbatch is 10:90.
[0052] 2. Preparation of cable material B: 50 kg of ethylene-vinyl acetate copolymer, 25 kg of linear low-density polyethylene, 140 kg of active inorganic flame retardant, 3 kg of stearic acid, 1 kg of carbon black, 2 kg of antioxidant, 3 kg of organotin, and 10 kg of flame retardant additive were mixed evenly. Then, 5 kg of compatibilizer and 1 kg of silicone masterbatch were added and mixed. The mixture was then fed into a screw extruder for extrusion granulation to obtain cable material B. The twin-screw extruder has a length-to-diameter ratio of 44:1; the temperatures of each section of the twin-screw extruder are as follows: 80℃~100℃, 125℃~130℃, 130℃~135℃, 135℃~140℃, 140℃~145℃, 145℃~150℃, 150℃~155℃; the die head temperature is 145℃~150℃; and the screw speed is 550 rpm. Among them, the active inorganic flame retardant is aluminum hydroxide; The antioxidant is a mixture of antioxidant 1024 0.5 kg, antioxidant 300 1 kg, and antioxidant DLTDP 0.5 kg; The flame retardant additive was prepared in Preparation Example 5.
[0053] 3. Preparation of cable material: Cable material A and cable material B are fed into a screw extruder for extrusion and granulation to obtain cable material; the length-to-diameter ratio of the twin-screw extruder is 44:1; the temperatures of each section of the twin-screw extruder are as follows: 80℃~100℃, 125℃~130℃, 130℃~135℃, 135℃~140℃, 140℃~145℃, 145℃~150℃, 150℃~155℃; the die head temperature is 145℃~150℃; and the screw speed is 550 rpm.
[0054] Example 3: A method for producing a room-temperature silane crosslinked, low-smoke, halogen-free flame-retardant cable material, comprising the following steps: 1. Preparation of cable material A: (1) Preparation of low-smoke halogen-free masterbatch: After mixing 70 kg of ethylene-vinyl acetate copolymer, 25 kg of polyolefin elastomer, 15 kg of linear low-density polyethylene, 200 kg of active inorganic flame retardant, 1.5 kg of polyethylene wax, 2.5 kg of carbon black, 4 kg of antioxidant, and 30 kg of flame retardant composite material evenly, 15 kg of compatibilizer and 2.5 kg of silicone masterbatch are added and mixed to obtain low-smoke halogen-free masterbatch. The active inorganic flame retardant is a mixture of 100 kg of aluminum hydroxide and 100 kg of magnesium hydroxide. The antioxidant is a mixture of 2 kg of antioxidant 1024 and 2 kg of antioxidant 300; The flame-retardant composite material was prepared in Preparation Example 3.
[0055] (2) Preparation of grafted masterbatch: 30 kg of ethylene-vinyl acetate copolymer, 20 kg of metallocene polyethylene, 70 kg of linear low-density polyethylene, and 3 kg of silane coupling agent were mixed and stirred to obtain graft masterbatch. Among them, the silane coupling agent is silane coupling agent A171; (3) Preparation of cable material A: Low-smoke halogen-free masterbatch and grafted masterbatch are fed into a screw extruder for extrusion and granulation to obtain cable material A. The twin-screw extruder has a length-to-diameter ratio of 44:1; the temperatures of each section of the twin-screw extruder are as follows: 80℃~100℃, 125℃~130℃, 130℃~135℃, 135℃~140℃, 140℃~145℃, 145℃~150℃, 150℃~155℃; the die head temperature is 145℃~150℃; and the screw speed is 550 rpm. The mass ratio of low-smoke halogen-free masterbatch to grafted masterbatch is 30:70.
[0056] 2. Preparation of cable material B: 70 kg of ethylene-vinyl acetate copolymer, 35 kg of linear low-density polyethylene, 160 kg of active inorganic flame retardant, 5 kg of stearic acid, 2 kg of carbon black, 4 kg of antioxidant, 5 kg of organotin, and 15 kg of flame retardant additive were mixed evenly. Then, 15 kg of compatibilizer and 3 kg of silicone masterbatch were added and mixed. The mixture was then fed into a screw extruder for extrusion granulation to obtain cable material B. The twin-screw extruder has a length-to-diameter ratio of 44:1; the temperatures of each section of the twin-screw extruder are as follows: 80℃~100℃, 125℃~130℃, 130℃~135℃, 135℃~140℃, 140℃~145℃, 145℃~150℃, 150℃~155℃; the die head temperature is 145℃~150℃; and the screw speed is 550 rpm. Among them, the active inorganic flame retardant is aluminum hydroxide; The antioxidant is a mixture of antioxidant 1024 1kg, antioxidant 300 1kg, and antioxidant DLTDP 2kg; The flame retardant additive was prepared in Preparation Example 6.
[0057] 3. Preparation of cable material: Cable material A and cable material B are fed into a screw extruder for extrusion and granulation to obtain cable material; the length-to-diameter ratio of the twin-screw extruder is 44:1; the temperatures of each section of the twin-screw extruder are as follows: 80℃~100℃, 125℃~130℃, 130℃~135℃, 135℃~140℃, 140℃~145℃, 145℃~150℃, 150℃~155℃; the die head temperature is 145℃~150℃; and the screw speed is 550 rpm.
[0058] Example 4: The difference from Example 1 is that the flame-retardant composite material was prepared by Preparation Example 2; and the flame-retardant additive was prepared by Preparation Example 5.
[0059] Example 5: The difference from Example 1 is that the flame-retardant composite material was prepared by Preparation Example 3; and the flame-retardant additive was prepared by Preparation Example 6.
[0060] Example 6: The difference from Example 1 is that the amount of flame-retardant composite material added is 20 kg.
[0061] Example 7: The difference from Example 1 is that the amount of flame-retardant composite material added is 30 kg.
[0062] Example 8: The difference from Example 1 is that the amount of flame retardant additive added is 10 kg.
[0063] Example 9: The difference from Example 1 is that the amount of flame retardant additive added is 15 kg.
[0064] Comparative Example 1: The difference from Example 1 is that no flame-retardant composite material is added.
[0065] Comparative Example 2: The difference from Example 1 is that no flame retardant additives are added.
[0066] Comparative Example 3: The difference from Example 1 is that the amount of flame-retardant composite material added is 19 kg.
[0067] Comparative Example 4: The difference from Example 1 is that the amount of flame-retardant composite material added is 31 kg.
[0068] Comparative Example 5: The difference from Example 1 is that the amount of flame retardant additive added is 9 kg.
[0069] Comparative Example 6: The difference from Example 1 is that the amount of flame retardant additive added is 16 kg.
[0070] Comparative Example 7: The difference from Example 1 is that cable material B is not added.
[0071] Performance testing: The performance of the cable materials prepared in the above embodiments and comparative examples was tested, as follows: Tensile strength: The tensile strength was determined according to the national standard GB / T 1040-2006 "Determination of tensile properties of plastics"; Oxidation induction time: Based on national standard GB / T 19466.6-2009 "Differential Scanning Calorimetry (DSC) for Plastics - Part 6: The determination of oxidation induction time (isothermal OIT) and oxidation induction temperature (dynamic OIT) was carried out to determine the induction time of the sample; the limiting oxygen index was determined by the national standard GB / T 2406-2008 "Test Method for Combustion Performance of Plastics" before and after 180 days of storage at room temperature. Smoke density: The smoke density of the samples before and after 180 days of storage at room temperature was determined according to the national standard GB / T 8323.2-2008 "Smoke generation of plastics - Part 2: Test method for determination of smoke density by single chamber method". Table 1 Performance Test Results As shown in Table 1, the cable material prepared using this application has stable and efficient flame retardant and smoke suppressant properties, as well as high mechanical strength and excellent comprehensive performance, and has important application value in the field of cable material technology.
[0072] Based on the test results of Example 1 and Comparative Example 1, it can be seen that the oxidation induction time, limiting oxygen index, limiting oxygen index after 180 days, smoke density, and smoke density after 180 days of storage of Example 1 are all better than those of Comparative Example 1, indicating that the addition of flame-retardant composite material effectively improves the flame-retardant performance of cable material.
[0073] Based on the test results of Example 1 and Comparative Example 2, it can be seen that the oxidation induction time, limiting oxygen index, limiting oxygen index after 180 days, smoke density, and smoke density after 180 days of storage of Example 1 are all better than those of Comparative Example 2, indicating that the addition of flame retardant additives effectively improves the flame retardant performance of cable materials.
[0074] Based on the test results of Examples 1, 6, 7, Comparative Example 3, and Comparative Example 4, it can be seen that the amount of flame-retardant composite material added affects the flame-retardant performance of the cable material, and the flame-retardant performance of the cable material is optimal when the amount of flame-retardant composite material added is 20-30 kg.
[0075] Based on the test results of Examples 1, 8, 9, Comparative Example 5, and Comparative Example 6, it can be seen that the amount of flame retardant additive added affects the flame retardant performance of the cable material, and the flame retardant performance of the cable material is optimal when the amount of flame retardant additive added is 10-15 kg.
[0076] Based on the test results of Example 1 and Comparative Example 7, it can be seen that the tensile strength, oxidation induction time, limiting oxygen index, limiting oxygen index after 180 days, smoke density, and smoke density after 180 days of storage of Example 1 are all better than those of Example 7, indicating that the addition of cable material B effectively improves the tensile strength and flame retardant properties of the cable material.
Claims
1. A room-temperature silane crosslinked, low-smoke, halogen-free flame-retardant cable material, characterized in that: It includes cable material A and cable material B; cable material A includes low-smoke halogen-free masterbatch and grafted masterbatch; The low-smoke halogen-free masterbatch comprises the following raw material components in parts by weight: 50-70 parts of ethylene-vinyl acetate copolymer, 15-25 parts of polyolefin elastomer, 5-15 parts of linear low-density polyethylene, 160-200 parts of active inorganic flame retardant, 5-15 parts of compatibilizer, 1.5-2.5 parts of silicone masterbatch, 0.5-1.5 parts of polyethylene wax, 1.5-2.5 parts of carbon black, and 2-4 parts of antioxidant; The grafted masterbatch comprises the following raw material components in parts by weight: 10-30 parts of ethylene-vinyl acetate copolymer, 10-20 parts of metallocene polyethylene, 50-70 parts of linear low-density polyethylene, and 1-3 parts of silane coupling agent.
2. The room-temperature silane crosslinked, low-smoke, halogen-free flame-retardant cable material according to claim 1, characterized in that: The cable material B comprises the following raw material components in parts by weight: 50-70 parts of ethylene-vinyl acetate copolymer, 25-35 parts of linear low-density polyethylene, 140-160 parts of active inorganic flame retardant, 5-15 parts of compatibilizer, 1-3 parts of silicone masterbatch, 3-5 parts of stearic acid, 1-2 parts of carbon black, 2-4 parts of antioxidant, and 3-5 parts of organotin.
3. A room-temperature silane crosslinked, low-smoke, halogen-free flame-retardant cable material according to claim 1 or 2, characterized in that: The active inorganic flame retardant is at least one of aluminum hydroxide and magnesium hydroxide.
4. A room-temperature silane crosslinked, low-smoke, halogen-free flame-retardant cable material according to claim 1 or 2, characterized in that: The antioxidant is at least one of antioxidant 1024, antioxidant 300, and antioxidant DLTDP.
5. The room-temperature silane crosslinked, low-smoke, halogen-free flame-retardant cable material according to claim 1, characterized in that: The low-smoke halogen-free masterbatch also includes 20-30 parts by weight of flame-retardant composite material; the flame-retardant composite material includes the following raw material components in parts by weight: 45-55 parts of ammonium polyphosphate, 0.5-1.5 parts of alkylphenol polyoxyethylene ether, 5-15 parts of tetraethyl orthosilicate, 10-20 parts of aluminum hydroxide, 0.5-1.5 parts of carboxymethyl chitosan, 0.01-0.1 parts of magnesium hydroxide, and 1-2 parts of silane coupling agent.
6. The room-temperature silane crosslinked, low-smoke, halogen-free flame-retardant cable material according to claim 5, characterized in that: The preparation method of the flame-retardant composite material includes the following steps: Ammonium polyphosphate and alkylphenol polyoxyethylene ether were mixed, then tetraethyl orthosilicate was added and mixed again, followed by the addition of aluminum hydroxide and the mixture was filtered to obtain the first mixture. Carboxymethyl chitosan was dissolved in water to obtain a carboxymethyl chitosan solution; Magnesium hydroxide is dissolved in ethanol to obtain a magnesium hydroxide solution; The carboxymethyl chitosan solution and magnesium hydroxide solution were mixed and then centrifuged to obtain a second mixture. The first mixture, the second mixture, and the silane coupling agent are mixed to obtain a flame-retardant composite material.
7. The room-temperature silane crosslinked, low-smoke, halogen-free flame-retardant cable material according to claim 2, characterized in that: The cable material B further includes 10-15 parts by weight of flame retardant additives; the flame retardant additives include the following raw material components in parts by weight: 1-3 parts of chitosan oligosaccharide, 25-35 parts of tetrahydrofuran, 30-40 parts of triethylamine, 3-7 parts of phenylphosphodichloro, 1-5 parts of furfurylamine, and 40-60 parts of petroleum ether.
8. The room-temperature silane crosslinked, low-smoke, halogen-free flame-retardant cable material according to claim 7, characterized in that: The preparation method of the flame retardant additive includes the following steps: Chitosan oligosaccharide, tetrahydrofuran, and triethylamine were mixed, followed by the addition of phenylphosphodichloro, then furfurylamine, and finally petroleum ether. The mixture was then filtered to obtain the flame retardant additive.
9. The room-temperature silane crosslinked, low-smoke, halogen-free flame-retardant cable material according to claim 1, characterized in that: The mass ratio of the low-smoke halogen-free masterbatch to the grafted masterbatch is (10-30):(90-70).
10. A method for preparing the room-temperature silane crosslinked, low-smoke, halogen-free flame-retardant cable material according to any one of claims 1-9, characterized in that, The preparation method steps are as follows: Preparation of cable material A: After uniformly mixing ethylene-vinyl acetate copolymer, polyolefin elastomer, linear low-density polyethylene, active inorganic flame retardant, polyethylene wax, carbon black, antioxidant, and flame retardant composite material, compatibilizer and silicone masterbatch are added and mixed to obtain low-smoke halogen-free masterbatch. Ethylene-vinyl acetate copolymer, metallocene polyethylene, linear low-density polyethylene, and silane coupling agent are mixed and homogenized to obtain graft masterbatch. Low-smoke halogen-free masterbatch and grafted masterbatch are fed into a screw extruder for extrusion and granulation to obtain cable material A. Preparation of cable material B: After uniformly mixing ethylene-vinyl acetate copolymer, linear low-density polyethylene, active inorganic flame retardant, stearic acid, carbon black, antioxidant, organotin, and flame retardant additive, compatibilizer and silicone masterbatch are added and mixed. The mixture is then fed into a screw extruder for extrusion granulation to obtain cable material B. Preparation of cable materials: Cable material A and cable material B are fed into a screw extruder for extrusion and granulation to obtain cable material.